Value of MDCT Imaging in evaluation Focal Hepatic Lesions , based on Ultrasound Guided Biopsy - Naser, Faesal; Zezafon, Hasan; Ghanem, Hala (Latakia University Journal -Medical Sciences Series, 2018)
The study included 150 patients , admitted to the gastroenterology clinic at Al Assad University Hospital in Lattakia from 1/2/2015 to 1/8/2016 for 18 months, all of them underwent abdominal ultrasound to confirm the presence of a suspected hepatic lesion. All These patients underwent MDCT with injections for adequate study to th hepatic lesion is observed, All cases are followed, each according to their radiographic diagnosis, 68 patients undergoing to liver guided biopsy, 10 patients portal Angigraphy , 25 patients MRI with the injection, while 6 patients underwent surgical operation on the liver for diagnosis, and two patients refused any procedure In the light of these successive procedures, a final diagnosis of the hepatic lesion is compared with the radiographic diagnosis to study the diagnostic value of the MDCT in the evaluation of hepatic lesion The percentage of males was 52% while females 48%, and the age of the patients between 1 and 84 years, the results of the study were divided into three groups relative to the relationship formed between radiographic diagnosis and final real diagnosis: In the first group, There was no deference in the accuracy of the radiographic diagnosis with the real, was 72 patients, ie, 48% of the patients, including cystic and noncancerous lesions, hemangiomas, primary tumors except HCC. The second group consisted of 28 patients, 18.6% of patients with hepatocellular carcinoma. The results of our radiological study were statistically significant compared to the final diagnosis, which led to the application of the LI-RAD system 2014 to all patients The third group included 50 patients, 33.3% of the patients, who included patients with secondary hepatic tumors (metastases). The results of our radiological study were statistically significant compared with the final diagnosis, which led to the application of the perfusion factor and the volume factor on all patients in the sample to increase the diagnostic value Radiology. القيمة التشخيصية للطبقي المحوري متعدد الشرائح (MDCT) في تقييم آفات الكبد البؤرية بالاستناد إلى الخزعة الموجهة بالإيكو شملت الدراسة 150 مريضا من مراجعي العيادة الهضمية في مستشفى الأسد الجامعي باللاذقية من 1\2\2015 وحتى 1\8\2016 لمدة ثمانية عشر شهراً ، خضعوا جميعا لتصوير بالأمواج فوق الصوتية للبطن لتأكيد وجود آفة كبدية بؤرية مشتبه بها، ثم ليخضع هؤلاء المرضى لتصوير طبقي محوري متعدد الشرائح بخمس أطوار مع الحقن لدراسة كافية للأفة الكبدية المشاهدة ، يوضع بعدها توصيف مع تشخيص شعاعي للآفة ، ثم تتابع الحالات جميعها خلال الفترة المذكورة ، كل منها حسب التشخيص الشعاعي الخاص بها ، لتخضع الى اجراءات لاحقة تنوعت بين 67 مريضاً خضعوا لخزعة كبدية موجهة بالأمواج فوق الصوتية وبين 10 مرضى أجروا تصوير وعائي للجملة البابية ، وبين 25 مريضاً أجروا مرنان مغناطيسي لاحق للكبد مع الحقن ، في حين أجرى 6 مرضى عمل جراحي على الكبد للتشخيص ، ورفض مريضان أي اجراء لاحق ليكتفي بالمراقبة فقط ، أما باقي المرضى فجاء التشخيص من فئة النقائل الكبدية ليكتفى فقط بكشف الورم البدئي لتأكيد التشخيص . وعلى ضوء هذه الاجراءات المتلاحقة يوضع تشخيص نهائي للأفة الكبدية المشاهدة يقارن مع التشخيص الشعاعي لدراسة القيمة التشخيصية للطبقي المحوري متعدد الشرائح بأطواره المختلفة في تقييم الآفات الكبدية . أتت نسبة الذكور 52% في حين الاناث 48 %,وتراوحت أعمار المرضى بين 1 و84 سنة, قسمت تائج الدراسة إلى ثلالث مجموعات نسبة الى العلاقة المتشكلة بين التشخيص الشعاعي والتخيص الحقيقي النهائي : المجموعة الأولى : تساوت فيها دقة التشخيص الشعاعي مع الحقيقي دون أهمية احصائية بينهما ، شملت 72 مريض أي بنسبة 48 % من مرضى البحث، ضمت كل من الافات الناجمة عن شذوذ دوراني ، الافات السليمة الكيسية وغير الكيسية ، الاورام الوعائية ، الاورام البدئية باستثناء HCC . المجموعة الثانية : شملت 28 مريض أي بنسبة 18.6% من مرضى البحث ضمت مرضى سرطانة الخلية الكبدية ، جاءت نتائج دراستنا الشعاعية بفارق احصائي هام بالمقارنة مع التشخيص الحقيقي مما دفعنا الى تطبيق نظام LI-RAD لعام 2014 على جميع مرضى العينة لرفع القيمة التشخيصية الشعاعية المجموعة الثالثة : شملت 50 مريض ، أي بنسبة 33.3% من مرضى البحث ضمت مرضى الأورام الكبدية الثانوية أو النقائل الكبدية ، جاءت نتائج دراستنا الشعاعية بفارق احصائي هام بالمقارنة مع التشخيص الحقيقي مما دفعنا الى تطبيق عامل التروية، وعامل الحجم على جميع مرضى العينة لرفع القيمة التشخيصية الشعاعية